Hubungan Tingkat Risiko Postur Kerja dan Karakteristik Individu Dengan Tingkat Risiko Keluhan Low Back Pain Pada Perawat Bangsal Kelas III di Rumah Sakit PKU Muhammadiyah Surakarta - Dewi, Puspita Kurnia Ariek, Tarwaka, PGDip Sc, M.Erg, Dwi Astuti, SKM., M.Kes (2015)
Low back pain is one of the occupational diseases in hospital. Some of nurses at PKU Muhammadiyah Surakarta Hospital got this pain which partially experienced back pain. The porpuse of this research is to show whether the correlation level of risk work posture and individual characteristics with level of risk low back pain by the nurses Bangsal Class III at Hospital of PKU Muhammadiyah Surakarta. The method was used in this observasional research with cross sectional approach. The subject of research as many as 20 nurses by using total sampling. The research instrument was RULA (Rapid Upper Limb Assessment) for testing work posture and VAS (Visual Analog Scale) test was tool for testing low back pain. Spearman Rank (Rho) test was used to show correlation of risk work posture with risk of low back pain with significant level (α≤0,05). The result of work posture with low back pain was obtained p-value (0,033) and individual characteristics with low back pain was obtained (1) Age (p=0,050), (2) BMI (p=0,220), (3) work period (p=0,038) and (4) body health (p=0,456).. The concluded that there was correlation significant between risk of work posture, age, work period with low back pain and there was not correlation significant between BMI and body health with low back pain. For that, the nurses should be use the tools when handle patients, doing strecthing and the management of hospitals to provide education about ergonomics as well as considering a change of work rotation. Key word : work posture, low back pain , nurses